On Verbal Numbers in Arabic: Preliminary Remarks - Al-Sharkawi, Muhammad (Folia Orientalia, 2026)
This article shows that Classical Arabic expresses verbal number. Arabic, of all the Semitic language family, meets the typological tests of the languages expressing verbal number. In addition, I will show that Classical Arabic provides a morphological verb form to express number. I will, however, show that for the form to express verbal number it requires a combination of morphological and semantic conditions. Without which the designated form does not express number, but expresses transitivity or the transfer of agency. These conditions are: form II must come from a root that has a form I, form I must be the transitive meaning of the root and the root must express an instant action. Form II, therefore, does not exclusively express number. Verbal number in Arabic is conditional. However, I will also propose that when form II verb expresses number, it does not express the transfer of agency.